2021
DOI: 10.1371/journal.pone.0260435
|View full text |Cite
|
Sign up to set email alerts
|

Violence and sexual and reproductive health service disruption among girls and young women during COVID-19 pandemic in Nepal: A cross-sectional study using interactive voice response survey

Abstract: Introduction There is a paucity of data on the impact of COVID-19 pandemic on girls and young women. The study examines the prevalence and correlates of violence and sexual and reproductive health (SRH) service disruption among girls and young women during COVID-19 restrictions and lockdown. Methods An interactive voice response survey was conducted among girls and women aged 18–24 years between 10th March to 24th April 2021. The survey enrolled 1314 participants. Descriptive analysis was used to assess prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…IVR has previously been used in remote and humanitarian contexts including in Afghanistan, the Democratic Republic of the Congo (DRC), Ghana, Haiti, Niger, and Somalia to collect and disseminate information on a host of topics including food insecurity, cash transfers, aid presence, health behavior, and violence prevention [22][23][24][25][26][27][28][29]. It is a flexible system that lends itself to a range of different content and has effectively been used in low-and middle-income countries for both information collection and dissemination during the COVID-19 pandemic [30][31][32][33][34]. IVR can be used as a standalone tool, or can be combined with other tools/methods to augment data collection and dissemination as was done by the International Organization for Migration (IOM) in Cox's Bazaar, Bangladesh, where participants were screened using an IVR survey to identify those eligible to receive a call back with a specific needs assessment survey [23, 24,35].…”
Section: Introductionmentioning
confidence: 99%
“…IVR has previously been used in remote and humanitarian contexts including in Afghanistan, the Democratic Republic of the Congo (DRC), Ghana, Haiti, Niger, and Somalia to collect and disseminate information on a host of topics including food insecurity, cash transfers, aid presence, health behavior, and violence prevention [22][23][24][25][26][27][28][29]. It is a flexible system that lends itself to a range of different content and has effectively been used in low-and middle-income countries for both information collection and dissemination during the COVID-19 pandemic [30][31][32][33][34]. IVR can be used as a standalone tool, or can be combined with other tools/methods to augment data collection and dissemination as was done by the International Organization for Migration (IOM) in Cox's Bazaar, Bangladesh, where participants were screened using an IVR survey to identify those eligible to receive a call back with a specific needs assessment survey [23, 24,35].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings add to the growing body of literature about the impacts of COVID-19 on violence, which has so far found mixed evidence in Nepal as a whole, but some evidence of increased risk among subgroups. 38 , 40 Our study highlights that young married women in rural parts of Nepal who are already exposed to high levels of violence face increased rates of violence in a time of lockdown and crises like COVID-19.…”
Section: Discussionmentioning
confidence: 76%
“…Our analysis has included several risk factors for IPV against women, based on published literature and consistent with prior published analyses from this study. 14 , 35 , 38 At the individual level, participant baseline current age (continuous), caste (categorised as Brahmin/Chhetri, indigenous groups and so-called untouchables/religious minority groups), marriage type (love vs arranged marriage), receipt of dowry (yes/no), level of education (<6 years, 6–12 and over 12 years) and religion (Hindu vs non-Hindu) were included. Although shown in Table 1 for context, we did not include age at marriage or marriage duration into the models due to potential collinearity with age.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Dalit women are more likely to be the victims of violence, sexual assault, and harassment, which restrict their freedom of movement and prevents them from traveling. 12–15 , 25 , 37 , 38 The lower PNC use among Dalit women may also be related to poor self-awareness and lack of health information accessibility due to social bias. Many women in our study areas revealed that they were unaware of risky conditions and adverse events after delivery.…”
Section: Discussionmentioning
confidence: 99%